The acute effects of dynamic and ballistic stretching on vertical jump height, force, and power - Jaggers, J. R.; Swank, A. M.; Frost, K. L.; Lee, C. D. (The Journal of Strength and Conditioning Research, 2008)
Stretching before performance is a common practice among athletes in hopes of increasing performance and reducing the risk of injury. However, cumulative results indicate a negative impact of static stretching and proprioceptive neuromuscular facilitation (PNF) on performance; thus, there is a need for evaluating other stretching strategies for effective warm-up. The purpose of this study was to compare the differences between two sets of ballistic stretching and two sets of a dynamic stretching routine on vertical jump performance. Twenty healthy male and female college students between the ages of 22 and 34 (24.8 +/- 3 years) volunteered to participate in this study. All subjects completed three individual testing sessions on three nonconsecutive days. On each day, the subjects completed one of three treatments (no stretch, ballistic stretch, and dynamic stretch). Intraclass reliability was determined using the data obtained from each subject. A paired samples t-test revealed no significant difference in jump height, force, or power when comparing no stretch with ballistic stretch. A significant difference was found on jump power when comparing no stretch with dynamic stretch, but no significant difference was found for jump height or force. Statistics showed a very high reliability when measuring jump height, force, and power using the Kistler Quattro Jump force plate. It seems that neither dynamic stretching nor ballistic stretching will result in an increase in vertical jump height or force. However, dynamic stretching elicited gains in jump power poststretch.